The Efficiency of Centrifugation in the Detection of Mollicutes in Bovine Milk - Salina, Anelise [UNESP]; Lopes, Bruna Churocof; Barone, Fabiana Luccas [UNESP]; Langoni, Helio [UNESP] (MDPI, 2023)
Mastitis is one of the main diseases that affects dairy cattle. It is characterized by a multifactorial disease with multiple etiologies including microorganisms such as bacteria, viruses, fungi, yeasts, and algae. Mastitis caused by Mycoplasma spp. results in a contagious nature of infection and has been studied much in Brazil. The objectives of this research were (1) to investigate in clinical mastitis milk samples, by conventional PCR, the presence of the following mycoplasma species: Mycoplasma (M.) bovis, M. bovirhinis, M. bovigenitalium, M. californicum, and M. alkalescens and (2) compare the PCR Mollicutes detection rates using previous concentration and homogenization steps of the milk samples. Of the 993 clinical mastitis milk samples analyzed, 13.7% (136/993) and 8.0% (80/993) were positive for the Mollicutes class after concentration and homogenization, respectively, and all of them were PCR-negative for the five species investigated. Of the 70 expansion milk tanks analyzed, all of them were PCR-negative for the Mollicutes class. The importance of the previous concentration of milk in the routine of molecular analysis was evidenced when compared to the results obtained only with homogenization.
Keywords: clinical mastitis; mammary mycoplasmosis; Mycoplasmaspp; PCR